Calcaneal tuberosity fractures through prior Schantz pin sites in patients with diabetic neuropathy. (June 2019) - Ramsey, Duncan C.; Laursen, Rachel K.; Meeker, James; Yoo, Brad
Highlights: Brief Summary What is Known? Schantz pin placement in the calcaneal tuberosity is a common procedure especially in spanning external fixator of the ankle. Common complications of Schantz pins placement are pin site infections and nerve injuries. Fractures through Schantz pin sites is a known complication, reported nearly exclusively in diaphyseal bone. What This Study adds? This study reports three diabetic patients that sustained post instrumentation fractures of the calcaneus through external fixator pin-sites. The cause of this complication is likely related to diabetic neuropathy causing insensate foot and the biomechanical compromised location of the pin site. Surgeons should be cognizant of this iatrogenic complication of a common surgical procedure in diabetic patients. Abstract: Schantz pin placement in the calcaneal tuberosity is a common procedure known to be complicated by pin site infections and nerve injuries. Fractures through Schantz pin sites has been reported mostly in diaphyseal bone. This case series highlights three patients with type 2 diabetes mellitus and diabetic neuropathy who were fixed in an external fixator frame with a pin through the calcaneal tuberosity. At an average of 13 weeks, the patients presented with fracture through the pin site at the calcaneal tuberosity. One patient was treated with open reduction and internal fixation of the calcaneus and two patients were treated nonoperatively. These cases suggest that placement of calcaneal pins in patients with diabetic neuropathy harbors risk of iatrogenic fracture, a complication that has not been reported in the literature.